4-aminopyridine induced rage reaction in mice - Xu Jian-hua; Liu He-chu; Zhang Yuan-pei (Acta Pharmacologica Sinica, 2016)
Rage reaction was induced in mice by sc 4-aminopyridine (4-AP) 6 mg . kg-1. Mice appeared hyperreactive after 8-12 min and then squeaked and fought each other. These manifestations were most distinct in 10-30 min and subsided after 40-60 min. The occurrence of rage reaction on this dose level was around 90%. At higher doses 4-AP caused convulsions and death after evocation of rage reaction. The ED50 of 4-AP for eliciting rage reaction was 4.7 +/- 0.7 mg . kg-1 sc. No significant difference in induction of rage reaction was seen between male and female mice of different body weights. Both neuroleptic drugs (chlorpromazine, haloperidol, tarden and clozapine) and anxiolytic drugs (diazepam, chlordiazepoxide, and meprobamate) inhibited 4-AP-induced rage reaction in mice. Barbiturates, Chloral hydrate, methaqualone, morphine hydrochloride, aspirin, phenytoin sodium, diphenhydramine hydrochloride, atropine sulfate, and procaine hydrochloride did not affect rage reaction. The 4-AP-induced aggressive behavior, similar to that induced by electric footshock or isolation, has the merits of convenience to deal with and time saving. Hence we recommended it as a screening method for drugs with neuroleptic and anxiolytic activities.